Financial Distress, Company Growth, and Going Concern Audit Opinions: The Moderating Effect of Firm Size - Abdul Hafidz; Rita Yuniarti (Economics and Digital Business Review, 2026)
Financial distress has a significant effect on the issuance of going concern audit opinions. Companies experiencing greater financial difficulties are more likely to receive a going concern audit opinion because such conditions increase uncertainty regarding their ability to continue operations in the future. Company growth significantly influences going concern audit opinions. Firms with stronger growth tend to demonstrate better operational performance and more favorable business prospects, reducing the likelihood of receiving a going concern audit opinion. Company growth serves as a positive signal regarding business sustainability and future performance.Firm size is found to moderate the relationship between financial distress and going concern audit opinion. Financial distress on the probability of receiving a going concern opinion varies according to the size of the company. Larger firms generally possess greater resources and financial flexibility, which may reduce concerns regarding their ability to survive financial difficulties.Firm size does’nt moderate the relationship between company growth and going concern audit opinion. This result suggests that the influence of company growth on auditors’ assessments of going concern remains relatively consistent regardless of the company’s size. Firm size neither strengthens nor weakens the effect of company growth on the likelihood of receiving a going concern audit opinion.